Pengaruh Online Customer Review dan Brand Ambassador terhadap Keputusan Pembelian Produk Whitelab di Shopee - Fadia Putri; Efni Siregar; Ratna Dewi; Safaruddin Safaruddin; Irwan Musriza Harahap (Trending: Jurnal Manajemen dan Ekonomi, 2025)
Many series of skincare products are offered and sold offline and online. The large number of products that are popping up makes competition in the skincare product market even tighter. So there are many ways that sellers/shops use e-commerce such as Shopee to attract consumers to buy products, such as Whitelab. Apart from hoping for positive reviews, Whitelab also uses Brand Ambassadors for each product. The sampling technique in this research is nonprobability sampling. The sampling technique used in this research is the Accidental Sampling Technique. using SPSS version 26. Based on the results of this research, it is known that Online Customer Reviews do not have a significant influence on Purchasing Decisions, and Brand Ambassadors have a significant influence on Purchasing Decisions. Apart from that, simultaneously (F Test) it is known that Online Customer Reviews and Brand Ambassadors simultaneously or together have a positive and significant effect on Purchasing Decisions. The Adjusted R value for the Determinant Coefficient is 0.248 or 24.8%, while the remaining 75.2% is influenced by other variables that are not in this research such as: price, brand image, brand image, brand experience, and product quality. This research obtained 100 respondents, of which 50 were USU students, and 50 were Medan State Polytechnic students, with gender 23 men and 77 women, and an age range of 18 to 25 years.